The first iron(III) complexes with cyclin-dependent kinase inhibitors: Magnetic, spectroscopic (IR, ES+ MS, NMR, (57)Fe Mössbauer), theoretical, and biological activity studies - Trávnícek, Zdenek; Popa, Igor; Cajan, Michal; Zboril, Radek; Krystof, Vladimír; Mikulík, Jirí (Journal of inorganic biochemistry, 2010)
The first Fe(III) complexes 1-6 with cyclin-dependent kinase (CDK) inhibitors of the type [Fe(L(n))Cl(3)].nH(2)O (n=0 for 1, 1 for 2, 2 for 3-6; L(1)-L(6)=C2- and phenyl-substituted CDK inhibitors derived from 6-benzylamino-9-isopropylpurine), have been synthesized and characterized by elemental analysis, IR, (57)Fe Mössbauer, (1)H and (13)C NMR, and ES+ mass spectroscopies, conductivity and magnetic susceptibility measurements, and thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The study revealed that the compounds are mononuclear, tetrahedral high-spin (S=5/2) Fe(III) complexes with an admixture of an S=3/2 spin state originating probably from five-coordinated Fe(III) ions either connecting with a bidentate coordination mode of the CDK inhibitor ligand or relating to the possibility that one crystal water molecule enters the coordination sphere of the central atom in a portion of molecules of the appropriate complex. Nearly spin-only value of the effective magnetic moment (5.82micro(eff)/micro(B)) was determined for compound 1 due to absence of crystal water molecule(s) in the structure of the complex. Based on NMR data and DFT calculations, we assume that the appropriate organic ligand is coordinated to the Fe(III) ion through the N7 atom of a purine moiety. The cytotoxicity of the complexes was tested in vitro against selected human cancer cell lines (G-361, HOS, K-562 and MCF-7) along with the ability to inhibit the CDK2/cyclinE kinase. The best cytotoxicity (IC(50): 4-23muM) and inhibition activity (IC(50): 0.02-0.09microM) results have been achieved in the case of complexes 2-4, and complexes 3, 4 and 6, respectively. In addition, the X-ray structure of 2-chloro-6-benzylamino-9-isopropylpurine, i.e. a precursor for the preparation of L(1), L(4) and L(5), is also described.
Keywords: Purines; inhibiční proteiny cyklin-dependentních kinas; protinádorové látky; Cell Line, Tumor; spektrální analýza; Drug Screening Assays, Antitumor; železo; Spectrum Analysis; molekulární struktura; Molecular Structure; puriny; Electrochemical Techniques; molekulární modely; elektrochemické techniky; Models, Molecular; Animals; lidé; Cyclin-Dependent Kinase Inhibitor Proteins; Iron; Humans; zvířata; screeningové testy protinádorových léčiv; nádorové buněčné linie; Antineoplastic Agents